Collaborative Commitments. - Grayson, David (Community Links, 2008)
It is easy to become demoralised and paralysed by the scale and number of seemingly intractable problems we face in the UK and globally. Rather, we should treat those problems as the spur to innovation. As Albert Einstein once said, “we can’t solve problems by using the same kind of thinking we used when we created them.” Challenging times demand new approaches – but also provide a sense of possibility. That is the philosophy of the Council on Social Action (CoSA). One of CoSA’s ideas is the concept of ‘collaborative commitments’.
This ‘Collaborative Commitments’ think-piece has been prepared for the Council on Social Action (CoSA) by the new Doughty Centre for Corporate Responsibility at the Cranfield School of Management. (www. doughtycentre.info) This work is supported by Allen & Overy LLP and the Royal Mail Group. The think-piece is commissioned by and prepared for the Council on Social Action, but it is not a policy statement of CoSA.